The Role of Job Competency Among Workload, Environment, and Compensation on Performance (A Study of the Social Service, Women's Empowerment, and Child Protection Office, Kulon Progo Regency, Indonesia) - Zuliyanti Zuliyanti; Ferri Kuswantoro; Eni Andari; Mohamad Najmudin (Riviera Publishing, 2026)
This study investigates the role of job competency as a mediating variable in the relationship between workload, work environment, compensation, and employee performance. Conducted at the Social Service for Women's Empowerment and Child Protection in Kulon Progo Regency, Indonesia, the research addresses a critical gap in understanding how internal factors influence performance within public social services. Using a census method, data were collected from 139 employees and analyzed using Structural Equation Modelling (SEM) with AMOS 22. The findings reveal that workload, work environment, and compensation each have a positive and significant direct effect on both employee competency and performance. Furthermore, work competency demonstrates a significant positive effect on performance and serves as a crucial partial mediator in the relationships between the exogenous variables and employee performance. These results imply that strategic investments in competency development can amplify the positive effects of manageable workloads, supportive environments, and fair compensation on overall performance.